Olaparib and Doxorubicin Co-Loaded Polypeptide Nanogel for Enhanced Breast Cancer Therapy - Liu, Yanhong; Wang, Meiyan; Liu, Wanru; Jing, Jili; Ma, Hongshuang (Frontiers in Bioengineering and Biotechnology, 2022)
Although great progress has been made in improving the efficacy of cancer treatment through combination treatment using drug agents, there are still challenges in improving the efficiency of drug delivery. In this study, olaparib and doxorubicin were co-loaded on disulfide bond cross-linked polypeptide nanogels for the treatment of breast cancer in mouse models. Under stimulation of a high glutathione environment in cancer cells, the drug is quickly released from the nanogel to target cancer cells. In addition, compared with free drugs and single-drug-loaded nanogels, dual-drug- co-loaded nanogels exhibit the best anti-cancer effect and demonstrated excellent biological safety. Therefore, the co-delivery of olaparib and doxorubicin through polypeptide nanogels presents good prospects for application as anti-cancer treatment.